1978
DOI: 10.1007/bf00560463
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology in normal volunteers of praziquantel, a new drug against schistosomes and cestodes

Abstract: The tolerance of Praziquantel (2-cyclohexylcarbonyl-1, 3, 4, 6, 7, 11b-hexahydro-2H-pyrazino-[2, 1-a]isoquinoline-4-one) in oral doses of 1 X 20 mg/kg, 1 X 50 mg/kg, 3 X 10 mg/kg and 3 X 25 mg/kg body weight (tau = 4 h) was tested in a complex study involving 36 healthy volunteers. In addition to the usual assessment of clinical chemistry, haematology, coagulation physiology, urinalysis, clinico-physiological examination including EEG, and medical examination, clinico-psychological parameters were also recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
4

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 15 publications
2
58
0
4
Order By: Relevance
“…Praziquantel has a short half life, thus decreasing the drug plasma level (Leopold et al 1978) would decrease the frequency of adverse effects. The 2 h interval between drug intake proved difficult to manage in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Praziquantel has a short half life, thus decreasing the drug plasma level (Leopold et al 1978) would decrease the frequency of adverse effects. The 2 h interval between drug intake proved difficult to manage in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Most investigators have reported good tolerability of praziquantel. 13,14 Some patients present some side effects including fever, headache, nausea, vomiting, dizziness, meningismus, increased intracranial pressure, 11,12 and cerebral infarct. These adverse reactions are probably not due to a toxic effect of praziquantel but rather to an inflammatory reaction produced by the host in response to massive destruction of cysticerci in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic data of different doses of PZQ are few and old, and have been obtained in healthy volunteers rather than in schistosome-infected patients (Leopold et al 1978). An exponential increase was found in the area under the curve (AUC) with the PZQ dose in the range of 5 to 50 mg/kg, with a six-fold increase from 20 to 50 mg/kg (Leopold et al 1978). However, these data do not come from infected patients, and hence cannot be extrapolated so easily.…”
Section: Public Health Implicationsmentioning
confidence: 99%